An Interplay among FIS, H-NS, and Guanosine Tetraphosphate Modulates Transcription of the Escherichia coli cspA Gene under Physiological Growth Conditions - Brandi, Anna; Giangrossi, Mara; Giuliodori, Anna M.; Falconi, Maurizio (Frontiers in Molecular Biosciences, 2016)
CspA, the most characterized member of the csp gene family of Escherichia coli, is highly expressed not only in response to cold stress, but also during the early phase of growth at 37°C. Here, we investigate at molecular level the antagonistic role played by the nucleoid proteins FIS and H-NS in the regulation of cspA expression under non-stress conditions. By means of both probing experiments and immunological detection, we demonstrate in vitro the existence of binding sites for these proteins on the cspA regulatory region, in which FIS and H-NS bind simultaneously to form composite DNA-protein complexes. While the in vitro promoter activity of cspA is stimulated by FIS and repressed by H-NS, a compensatory effect is observed when both proteins are added in the transcription assay. Consistently with these findings, inactivation of fis and hns genes reversely affect the in vivo amount of cspA mRNA. In addition, by means of strains expressing a high level of the alarmone guanosine tetraphosphate ((p)ppGpp) and in vitro transcription assays, we show that the cspA promoter is sensitive to (p)ppGpp inhibition. The (p)ppGpp-mediated expression of fis and hns genes is also analyzed, thus clarifying some aspects of the regulatory loop governing cspA transcription.